Lois González, Rubén C. y Pino, Daniel (coords.) (2015). A Galicia urbana - Miramontes Carballada, Ángel (Documents d’Anàlisi Geogràfica, 2017)
Lois González, Rubén C. y Pino, Daniel (coords.) (2015) A Galicia urbana Vigo (Pontevedra): Edicións Xerais Galicia, 755 p. ISBN 978-84-9914-930-1